DEVELOPMENT OF AN ORIGINAL METHOD AND TECHNICAL ASPECTS OF ENDOSCOPIC HEMOSTASIS IN EXPERIMENTAL GASTRODUODENAL BLEEDING (World Bulletin of Public Health, 2023)
Despite many years of research into this pathology, against the background of pharmacological and endoscopic methods of correction that were discovered by the beginning of the 21st century, the treatment of complications of ulcerative lesions of the gastric mucosa and duodenum still remains a complex problem in modern gastroenterology
Keywords: ulcerative; gastroenterology; treatment; beginning